Hungarian Monitoring, 29 September 1989 . [Magyar rádiófigyelő], 1989. szeptember 29 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Poland: Walesa, Solidarity, Polish United Workers' Party - On the "New Forum" in the GDR Domestic Affairs: - Armed Forces Day - Demonstrations to dissolve Workers' Militia - Three party initiative's conference of experts - East German refugees Economy: - Preparations to set up State Audit Office - Group of Western investors buys Skála shares worth HUF 587 million Külpolitika: - Lengyelország: Walesa , Szolidaritás, LEMP - Az NDK-ban működő Új Fórumról Belpolitika: - Fegyveres Erők Napja - Tüntessek a Munkásőrség feloszlatására - Három párti kezdeményezés szakértői konferenciája - Kelet-német menekültügy Gazdaság: - Az Állami Számvevőszék intézményének előkészítése - Egy nyugati befektető csoport 587 millió forintért vett SKÁLA részvényeket